The Impact of Collaborative Strategic Reading and Cognitive Style on Students’ Reading Comprehension in Senior High School - Bachtiar, Abdul Hamid (Universitas Pendidikan Ganesha, 2024)
This study was motivated by the fact that most students face difficulties in comprehending reading texts due to the lack of appropriate reading strategies. Therefore, teachers need to implement effective reading strategies, such as Collaborative Strategic Reading (CSR). This study aims to analyze the impact of CSR and cognitive styles on students' reading comprehension. The study employed an experimental design involving 130 tenth-grade high school students. Data were collected using test methods, with instruments comprising cognitive style tests and reading comprehension tests. Data analysis was conducted using Analysis of Variance (ANOVA). The results of the study indicated the following: first, there was a significant difference in reading comprehension between students taught using CSR and those taught with SQ3R (significance value 0.00 < 0.05); second, there was a significant difference in reading comprehension between students with Field-Independent (FI) and Field-Dependent (FD) cognitive styles (significance value ρ < 0.05); third, there was a significant interaction effect between reading strategies and cognitive styles on reading comprehension (t-test value 20.252, ρ < 0.05). Based on these findings, it can be concluded that CSR is proven effective in improving reading comprehension and can serve as an alternative reading strategy in the learning process.